Análise das técnicas de microarranjos e RNAseq através da ontologia ontocancro - Nascimento, Karlise Soares (2013)
The research on molecular interactions which cause genetic diseases has been the focus of many studies in recent years. With the inclusion of informatics in biological research, there was a great advance in the discovery of new solutions and diagnostic techniques for the treatment of diseases. Cancer is one of the diseases that have caused more interest among scientists around the world, and between their variations, are those caused by genetic defects that affect the genome maintenance mechanisms (GMM), which promote the proper functioning of the organism of an individual. Halazonetis and colaborators (2008) published a study involving of the metabolic pathways GMM, which identifies the appearance of a barrier that prevents the spread of cancer, but it is broken by initiating uncontrolled reproduction of defective cells that cause the cancerous tumors. The motivation of this work is to investigate the process of activation of anticancer barrier, using quantitative methods to analysis of the expression of genes and pathways. For this reason, it was used the Ontocancro ontology as analysis tool, being made several changes in its architecture for the realization of this study.